Effect of cold stress on photosynthetic physiological characteristics and molecular mechanism analysis in cold-resistant cotton (ZM36) seedlings - Li, Youzhong; Zhu, Jincheng; Xu, Jianwei; Zhang, Xianliang; Xie, Zongming; Li, Zhibo (Frontiers in Plant Science, 2024)
Low temperature and cold damage seriously hinder the growth, development, and morphogenesis of cotton seedlings. However, the response mechanism of cotton seedlings under cold stress still lacks research. In this study, transcriptome sequencing, gas exchange parameters, and rapid chlorophyll fluorescence parameters were analyzed in leaves of cold-tolerant upland cotton variety “ZM36” under different temperature stress [25°C (T25, CK), 15°C (T15), 10°C (T10), and 4°C (T4)]. The results showed that the net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), PSII potential maximum photochemical efficiency (Fv/Fm), and performance index (PIabs) of cotton leaves significantly decreased, and the intercellular CO2 concentration (Ci) and Fo/Fm significantly increased under cold stress. The transcriptome sequencing analysis showed that a total of 13,183 DEGs were involved in the response of cotton seedlings at each temperature point (T25, T15, T10, and T4), mainly involving five metabolic pathways—the phosphatidylinositol signaling system, photosynthesis, photosynthesis antenna protein, carbon fixation in photosynthetic organisms, and carotenoid synthesis. The 1,119 transcription factors were discovered among all the DEGs. These transcription factors involve 59 families, of which 15.8% of genes in the NAC family are upregulated. Through network regulatory analysis, the five candidate genes GhUVR8 (GH_A05G3668), GhPLATZ (GH_A09G2161), GhFAD4-1 (GH_A01G0758), GhNFYA1 (GH_A02G1336), and GhFAD4-2 (GH_D01G0766) were identified in response to cold stress. Furthermore, suppressing the expression level of GhPLATZ by virus-induced gene silencing led to the reduction of low temperature resistance, implying GhPLATZ as a positive regulator of low temperature tolerance. The findings of the study revealed a piece of the complex response mechanism of the cold-tolerant variety “ZM36” to different cold stresses and excavated key candidate genes for low temperature response, which provided support for accelerating the selection and breeding of cotton varieties with low temperature tolerance.